2013
DOI: 10.1073/pnas.1306290110
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling migration models to the Americas with the variation of North American native mitogenomes

Abstract: In this study we evaluated migration models to the Americas by using the information contained in native mitochondrial genomes (mitogenomes) from North America. Molecular and phylogeographic analyses of B2a mitogenomes, which are absent in Eskimo–Aleut and northern Na-Dene speakers, revealed that this haplogroup arose in North America ∼11–13 ka from one of the founder Paleo-Indian B2 mitogenomes. In contrast, haplogroup A2a, which is typical of Eskimo–Aleuts and Na-Dene, but also present in the easternmost Sib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
87
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 78 publications
10
87
0
6
Order By: Relevance
“…This predates the Independence I (35) and Early Pre-Dorset (36) occupations by several thousand years and may be due to known dating problems from Arctic sites (37) and temporal smoothing of the maps. However, these dates support recent genetic evidence suggesting there was human activity in the general region around 6,000 y ago (38). By 4 ka, there are signs of occupation across the entire Canadian Arctic, and at 2.5 ka, site density increases to the south.…”
Section: Resultssupporting
confidence: 73%
“…This predates the Independence I (35) and Early Pre-Dorset (36) occupations by several thousand years and may be due to known dating problems from Arctic sites (37) and temporal smoothing of the maps. However, these dates support recent genetic evidence suggesting there was human activity in the general region around 6,000 y ago (38). By 4 ka, there are signs of occupation across the entire Canadian Arctic, and at 2.5 ka, site density increases to the south.…”
Section: Resultssupporting
confidence: 73%
“…6 However, this model has not been fully evaluated, in part, because researchers were unable to date their arrival, which instead could be inferred from entire mitochondrial genomes. 7 The last inhabitants of former Beringia, reflected genetically in the Yukaghir, Chukchi, Eskimo-Aleuts, Na-Dene, and Northwestern North American Indians, have been a focus of extensive comparisons between complete mtDNA sequences from Siberia and from North America. As a result, the Siberian affinities of major Native American mtDNA haploclusters (A-D), initially detected by comparing a few single-nucleotide polymorphisms of similar haplotypes from Eurasia and the Americas, [7][8][9][10][11][12][13][14] have been revised and extended.…”
Section: Introductionmentioning
confidence: 99%
“…7 The last inhabitants of former Beringia, reflected genetically in the Yukaghir, Chukchi, Eskimo-Aleuts, Na-Dene, and Northwestern North American Indians, have been a focus of extensive comparisons between complete mtDNA sequences from Siberia and from North America. As a result, the Siberian affinities of major Native American mtDNA haploclusters (A-D), initially detected by comparing a few single-nucleotide polymorphisms of similar haplotypes from Eurasia and the Americas, [7][8][9][10][11][12][13][14] have been revised and extended. It has become evident that the range of distinct lineages confined to the entire Eskimo Arctic is a subset of haplogroups A2a, A2b, D2a, and D4b1a2a1, though each of their evolutionary histories is far from being explicitly clear.…”
Section: Introductionmentioning
confidence: 99%
“…The Clovis First model lost favor as sites south of the LGM ice sheets, such as Monte Verde (Chile), the Gault locality (Texas), Manis (Washington), and Paisley (Oregon), provided archaeological evidence that humans were present in the Americas at least a millennium before the appearance of Clovis technology (13). At the same time, genetic analyses suggested that New World founding populations began dispersing from Beringia ∼15,000-20,000 cal y BP (14)(15)(16).…”
mentioning
confidence: 99%